Th2 predominance and decreased NK cells in patients with hereditary angioedema - Sundler Björkman, Linda; Elmér, Evelina; Egesten, Arne; Skattum, Lillemor (Frontiers in Immunology, 2025)
BackgroundIn this study we included patients with hereditary angioedema (HAE) caused by decreased levels of C1 inhibitor (HAE-C1INH). An increased risk of autoimmune disorders, particularly systemic lupus erythematosus (SLE), has been reported in HAE-C1INH. This suggests that complement consumption affects adaptive immunity.ObjectiveTo investigate lymphocyte subpopulations in relation to disease activity and complement activation in HAE-C1INH patients and matched controls.MethodsFlow cytometry of peripheral blood lymphocyte populations, measurements of complement and complement fragments, and collection of clinical data.ResultsNK cell counts were lower in HAE-C1INH patients, and their frequencies were related to disease activity. The T helper (Th) cell balance was skewed towards more Th2 cells and less Th1 cells in HAE-C1INH patients compared to controls. There were also lower frequencies of class-switched B cells and plasmablasts in patients. Levels of C4 and the complement activation fragment C3d were related to disease activity.ConclusionsBlood lymphocyte populations are altered in HAE-C1INH, a finding which may be of pathophysiological importance considering the increased risks of both autoimmunity and allergy associated with HAE-C1INH.